Integration of Sustainable Development Goals (SDGs) into Institutional Development Strategy: Recommendations for Vietnamese Universities - Le, Hao Van; Nguyen, Cuong Huu (Vietnam Journal of Education, 2023)
The 17 Sustainable Development Goals (SDGs) of the 2030 Agenda for Sustainable Development, which were endorsed by global leaders at a United Nations meeting in September 2015, entered into force on January 1st, 2016. These objectives seek to coordinate worldwide endeavours to end inequality, combat climate change, and eradicate all forms of poverty while guaranteeing that no one is left behind. This study focuses on synthesizing reports and scholarly papers discussing the integration of the United Nations’ 17 SDGs into higher education worldwide to propose recommendations for Vietnam. The results from document analysis show that universities play a significant role in the implementation of the SDGs. Moreover, the key areas to integrate the SDGs into the institution’s strategic planning are education, research, cooperation and community services, and institutional governance and operations. It is suggested that to integrate the SDGs into the development strategy, Vietnamese universities should understand the SDGs, conduct a sustainable assessment, build sustainability policies, engage stakeholders, and regularly monitor and report progress toward the SDGs.